Trail (TNF-related apoptosis-inducing ligand) induces an inflammatory response in human adipocytes - Verena Zoller (Nature Portfolio, 2017)
Abstract High serum concentrations of TNF-related apoptosis-inducing ligand (TRAIL), a member of the tumor necrosis factor protein family, are found in patients with increased BMI and serum lipid levels. In a model of murine obesity, both the expression of TRAIL and its receptor (TRAIL-R) is elevated in adipose tissue. Accordingly, TRAIL has been proposed as an important mediator of adipose tissue inflammation and obesity-associated diseases. The aim of this study was to investigate if TRAIL regulates inflammatory processes at the level of the adipocyte. Using human Simpson-Golabi-Behmel syndrome (SGBS) cells as a model system, we found that TRAIL induces an inflammatory response in both preadipocytes and adipocytes. It stimulates the expression of interleukin 6 (IL-6), interleukin 8 (IL-8) as well as the chemokines monocyte chemoattractant protein-1 (MCP-1) and chemokine C-C motif ligand 20 (CCL-20) in a time- and dose-dependent manner. By using small molecule inhibitors, we found that both the NFκB and the ERK1/2 pathway are crucial for mediating the effect of TRAIL. Taken together, we identified a novel pro-inflammatory function of TRAIL in human adipocytes. Our findings suggest that targeting the TRAIL/TRAIL-R system might be a useful strategy to tackle obesity-associated adipose tissue inflammation.